2020
DOI: 10.1007/s00266-020-01892-y
|View full text |Cite
|
Sign up to set email alerts
|

Dual-Plane Retro-pectoral Versus Pre-pectoral DTI Breast Reconstruction: An Italian Multicenter Experience

Abstract: Background The use of conservative mastectomies has risen significantly during the last few years. The reconstructive choice of direct-to-implant reconstruction has become more practicable with modern mastectomy techniques. The initial trend in Italian centers was to use dualplane hybrid reconstruction. However, a high level of complications has been registered. From 2015 onward, in our centers, a pre-pectoral approach has been adopted. The authors sought to describe the Italian trend to gradually discard the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
57
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(62 citation statements)
references
References 54 publications
3
57
0
2
Order By: Relevance
“…Over the years, different techniques have been introduced in order to improve aesthetic and functional results in breast reconstruction. The use of prosthetic breast reconstruction has risen significantly, becoming the most frequent choice [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…Over the years, different techniques have been introduced in order to improve aesthetic and functional results in breast reconstruction. The use of prosthetic breast reconstruction has risen significantly, becoming the most frequent choice [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…A multicenter large study reported by Ribuffo et al comparing prepectoral (207 breasts) and subpectoral reconstruction (509 breasts) with ADM reported overall complication significantly higher in the subpectoral group mainly attributed to seroma and hematoma formation and animation deformity, which were significantly higher in the subpectoral group. 23 Incidence of wound dehiscence was 1.9% in the prepectoral group and 2.5% in the subpectoral group, which was not statistically significant. All patients in the above study had a minimum follow-up of 1 year, and the incidence of implant loss was 2.4% in the prepectoral group compared with 3.9% in the subpectoral group, which was not statistically significant.…”
Section: Discussionmentioning
confidence: 70%
“…29 This could activate innate immunity at the implant interface more than muscle and would be consistent with the increased capsular contracture rate observed in subglandular breast augmentation. 3,5,30 Collectively, these data all suggest that the adjacent tissue type could locally direct periprosthetic inflammation, which could in turn explain the difference in capsular contracture observed clinically based on implant insertion plane.…”
Section: Cellular and Molecular Origin Of Capsular Contracturementioning
confidence: 86%
“…4,6 In contrast, during breast reconstruction submuscular implant poses a greater risk of capsular contracture, affecting up to 8.7% of patients with prepectoral reconstruction with ADM and up to 13.9% of patients with subpectoral reconstruction. 5,6 Intraoperative maneuvers and manipulation of the breast implant can also reduce the risk of capsular contracture by utilizing the "14-point plan. [55][56][57] Steps 1 to 7 have already been described, and they include administering proper prophylactic antibiotics, avoiding periareolar incisions, using nipple shields, atraumatic dissection of a subpectoral pocket, meticulous hemostasis, and utilization of a triple antibiotic solution on the implant and breast pocket.…”
Section: Surgical Techniquementioning
confidence: 99%
See 1 more Smart Citation